2016
DOI: 10.1016/j.scico.2016.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Model-based mutation testing—Approach and case studies

Abstract: This paper rigorously introduces the concept of model-based mutation testing (MBMT) and positions it in the landscape of mutation testing. Two elementary mutation operators, insertion and omission, are exemplarily applied to a hierarchy of graph-based models of increasing expressive power including directed graphs, event sequence graphs, finite-state machines and statecharts. Test cases generated based on the mutated models (mutants) are used to determine not only whether each mutant can be killed but also w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 52 publications
0
37
0
1
Order By: Relevance
“…Here, we briefly discuss these approaches. For a detailed description and discussion on this subject, we point the reader to the specialised survey of Belli et al [30].…”
Section: Model-based Testingmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we briefly discuss these approaches. For a detailed description and discussion on this subject, we point the reader to the specialised survey of Belli et al [30].…”
Section: Model-based Testingmentioning
confidence: 99%
“…Despite this, we see a growing interest towards this direction. There is a recent dedicated survey on this subject [30] and multiple high profile publications over the last couple of years. Additionally, very recently efficient and scalable tools have been built, e.g., the VIBeS tool [12], which hopefully will push the research in this area further.…”
Section: Open Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding behavioural models, Aichernig et al [8] developed a mutation-based test generation technique for state machines. Belli et al [26] compare mutation-testing strategies when applied on event-based and state-based models, and found that both had similar effectiveness.…”
Section: Related Workmentioning
confidence: 99%
“…Nowadays, the application area of mutation testing is not limited to assessing test cases at implementation level only. A number of works have shown examples of applying it to different formalisms, at various levels of software development, and for assessment, as well as for generation of test cases [14][15][16][17][18][19][20][21][22][23][24]. Works dedicated to mutation testing-based generation of test cases usually share the idea of mutating a system, its model, or specification and then selecting test cases being able to detect the mutants [15,18,19,[23][24][25][26].…”
Section: Mutation Testingmentioning
confidence: 99%